1970
DOI: 10.1136/bmj.2.5706.396
|View full text |Cite
|
Sign up to set email alerts
|

Insulin Secretion in Heart Failure

Abstract: Summary: Insulin secretion tests were carried out before and after treatment in patients with severe congestive heart failure. Before treatment the plasma insulin level and the insulin secretion response to intravenous tolbutamide were significantly reduced in all patients. In patients who made a good clinical recovery the plasma insulin level and the insulin secretion response were significantly improved. Patients who had a poor response to medical treatment showed little improvement in their insulin secretio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
9
0

Year Published

1970
1970
2011
2011

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…One physiological role of such a system may be to protect normal individuals from ketoacidosis during periods of great stress such as burns, severe congestive heart fail-ure, and myocardial infarction. Although these states have been associated with increased catechol output (11)(12)(13) and severe inhibition of acute insulin release (14)(15)(16), the maintenance of normal or elevated basal insulin levels appears adequate to suppress lipolysis and may account for the rarity of ketoacidosis in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…One physiological role of such a system may be to protect normal individuals from ketoacidosis during periods of great stress such as burns, severe congestive heart fail-ure, and myocardial infarction. Although these states have been associated with increased catechol output (11)(12)(13) and severe inhibition of acute insulin release (14)(15)(16), the maintenance of normal or elevated basal insulin levels appears adequate to suppress lipolysis and may account for the rarity of ketoacidosis in these conditions.…”
Section: Discussionmentioning
confidence: 99%
“…Though many factors may regulate insulin secretion, the dominating control exercised by the sympathetic nervous system is seen in a number of clinical situations. In patients with greatly increased sympathetic nervous activity due to cardiogenic shock (Allison et al, 1969;Taylor et al, 1969), severe heart failure (Sharma et al, 1970), hypothermia (Baum and Porte, 1968), and phaeochromocytoma (Wilber et al, 1966;Spergel et al, 1968;Colwell, 1969;Porte, 1969) the secretion of insulin is completely suppressed even though the blood glucose concentration is greatly raised. The insulin suppression in these patients is maintained even when challenged by such a potent insulinogenic stimulus as intravenous tolbutamide Majid et al, 1970;Sharma et al, 1970).…”
Section: Discussionmentioning
confidence: 99%
“…The normal insulin secretion response to glucose and tolbutamide is suppressed in patients with severe power failure of the heart, whether this is due to cardiogenic shock after myocardial infarction (Allison et al, 1969;Taylor et al, 1969), severe congestive heart failure (Sharma et al, 1970), or pumping failure after open-heart surgery . Evidence has suggested that one of the major factors responsible for this suppression of insulin secretion was the greatly increased sympathetic stimulation found in such patients Majid et al, 1970;Sharma et al, 1970).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is of considerable clinical interest in the light of the recent finding that insulin secretion is suppressed in patients with severe heart failure (Sharma, Majid, Pakrashi, Dykes & Taylor, 1970;Majid, Saxton, Dykes, Galvin & Taylor, 1970), particularly as digitalis glycosides are frequently employed in the treatment of these patients. However, as the relief of heart failure itself results in significant improvement in insulin secretion (Sharma et al, 1970; the direct importance of these glycosides in the relief of insulin suppression in such patients is difficult to define. Triner et al (1969) also suggested that the mechanism whereby ouabain exerted its hypoglycaemic activity was either by suppression of release of catecholamines or by interference with their metabolic effects.…”
mentioning
confidence: 97%